Navigating without vision: spontaneous use of terrain slant in outdoor place learning. Issue 3 (3rd July 2021) - Nardi, Daniele; Singer, Katelyn J.; Price, Krista M.; Carpenter, Samantha E.; Bryant, Joseph A.; Hatheway, Mackenzie A.; Johnson, Jada N.; Pairitz, Annika K.; Young, Keldyn L.; Newcombe, Nora S.
ABSTRACT: The topography of the land provides a suite of spatial information for navigation. In an outdoor field experiment, we examined terrain slant as a nonvisual cue. Without being told which cue to use, blindfolded, sighted participants completed a place-learning task in a flat and a slanted site. Errors were significantly smaller in the slanted site. Furthermore, performance in the slanted – but not flat – site was significantly better than expected if guessing the target's direction. This suggests that proprioceptive/kinesthetic and vestibular cues from the slant were spontaneously used for place-learning, albeit with lower accuracy compared to visual cues. Terrain slope might be an environmental cue that is salient and realistically used by blind and sighted persons.